Combined Aerobic Exercise and Virtual Reality-Based Upper Extremity Rehabilitation Intervention for Chronic Stroke: Feasibility and Preliminary Effects on Physical Function and Quality of Life - Ross, Ryan E.; Hart, Emerson; Williams, Ewan R.; Gregory, Chris M.; Flume, Patrick A.; Mingora, Christina M.; Woodbury, Michelle L. (Archives of rehabilitation research and clinical translation, 2023)
To (1) examine the feasibility of combining lower extremity aerobic exercise (AEx) with a virtual reality (VR) upper extremity (UE) rehabilitation intervention and (2) provide an estimate of effect size for the combined intervention on UE function, aerobic capacity, and health-related quality of life. Single-group feasibility trial. Research laboratory. Community-dwelling individuals with mild to moderate impairment of the UE at least 6 months post stroke (N=10; male, n=6; female n=4; mean age, 54 years). All participants received 18 sessions over a nominal 2-3 sessions per week schedule of a combined AEx and VR-UE rehabilitation intervention. During each session, participants completed 15 minutes of lower extremity AEx followed by playing a VR-UE rehabilitation game for approximately 20 minutes. Feasibility was evaluated by metrics of adherence, retention, treatment acceptability, data completeness, and adverse events. UE function, aerobic capacity (peak oxygen consumption [Vo2peak]), and quality of life were assessed with the Fugl-Meyer Assessment of Upper Extremity (FMA-UE), expired gas exchange analysis, and Stroke Impact Scale (SIS), respectively. Adherence was 100%, and there were no withdrawals or losses to follow-up to report. Participants completed the intervention in 49±14 days. Cohen's dz effect size calculations indicated the intervention elicited medium effects on FMA-UE (dz=0.50) and SIS memory domain (dz=0.46) and large effects on absolute Vo2peak (dz=1.46), relative Vo2peak (dz=1.21), SIS strength (dz=1.18), and SIS overall recovery domains (dz=0.81). Combining lower extremity AEx and VR-UE rehabilitation appears feasible in the clinical research setting. Fifteen minutes of lower extremity AEx performed at vigorous intensity appears to elicit clinically meaningful benefits in chronic stroke. Further examination of the combination of lower extremity AEx and VR-UE rehabilitation and its effects on physical function and quality of life is warranted.